Recurrent asthma exacerbations: co-existing asthma and common variable immunodeficiency. (3rd June 2022) - Ibrahim, H.; Walsh, J.; Casey, D.; Murphy, J.; Plant, B. J.; O'Leary, P.; Murphy, D. M.
Abstract: Introduction : Common variable immunodeficiency is characterized by impaired B-cell differentiation and defective immunoglobulin production manifesting as recurrent respiratory tract infections. While the condition can masquerade as asthma, late diagnosis of CVID in known asthmatic is rarely reported. Case Study : We present the case of a 43-year-old lady with recurrent episodes of wheeze, cough, sinusitis and multiple lower respiratory tract infections. Transiently responsive to antibiotics and steroids. These episodes had been occurring for many years and she had a longstanding clinical diagnosis of asthma. Results : As part of her work up for recurrent respiratory tract infections a CT thorax was performed and demonstrated bronchiectasis. Further tests including Immunoglobulin levels revealed critically low IgG, IgM, and IgA levels. Immunoglobulin replacement therapy was commenced with a reduction in exacerbation frequency and severity, and objective improvement of asthma control. Subsequent lung function tests demonstrated reversible airflow limitation (obstructive lung function with 13% reversibility in FEV1 post-bronchodilator) consistent with asthma. Conclusion : Our case illustrates the importance of searching for alternate and co-existent diagnoses in patients diagnosed with asthma who are unresponsive to conventional therapy. We believe that serum immunoglobulin measurement should form a component of such a workup.